Enhanced mechanical properties and biodegradability of polyvinyl alcohol and starch filled water hyacinth fibre biofilm - Din, Siti Nor; Othman, Muhammad Afiq; Hashim, Faiezah; Mohd Zaini, Nurul Aizan; Che Ismail, Nor Hafizah; Ahmad, Zuliahani (Universiti Teknologi MARA, Perlis, 2025)
Single-use plastic packaging that is difficult to biodegrade has been used extensively for several decades, contributing to pollution. As a result, the development of biodegradable plastic packaging has become essential to solve the ever-growing issue of disposing of plastic waste. Materials such as polyvinyl alcohol (PVA) and tapioca starch have been utilized in the creation of biodegradable biofilms. However, the addition of starch into PVA could reduce the strength and physical properties of biofilm due to the low mechanical properties of starch. Therefore, the main interest of this research is to investigate the mechanical and biodegradable properties of a biofilm composed of PVA and tapioca starch filled with water hyacinth fibres (WHF). The PVA/starch matrix was mixed with varying WHF loadings during the casting process, which produces the biofilm. Fourier Transform Infrared Spectroscopy (FTIR) analysis demonstrated a strong biofilm formation between the PVA/starch and WHF due to a good chemical interaction. Furthermore, the biofilm has become more stiff and rigid as a result of the addition of WHF, along with the increased in tensile strength and Young's modulus. However, the addition of WHF had consequently decreased the tensile strain at break of the biofilm. Because the biofilms were soluble in water, they lost weight when immersed in and stirred around in distilled water. Next, as the concentration of fibre increased, so did the biodegradability of the film. Based from the results, it can be inferred that 10% w/w was the ideal WHF loading, producing good mechanical, biodegradable and solubility qualities. Since it is a numerous and accessible material, using water hyacinth, which is frequently thrown away because it disturbs the aquatic ecosystem, in the process of producing biofilms is a promising alternative to the packaging industry.